(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Aims and Objectives: Cerebral ischemic stroke is the most common life threatening and disabling neurological diseases. There are many studies showing relationship between carotid artery stenosis and ischemic stroke. This study is done to assess the carotid artery morphology with the help of color Doppler sonography. Methodology: This is a cross sectional observational study carried out in neurology department of Dhaka National Medical College Hospital (DNMCH) during the period of July 2016 to January 2018 among 30 patients admitted with acute ischemic stroke. Dopplerultrasound was performed during hospitalization to find out carotid artery stenosis. Statistics analysis was done with STATA 10. Results: Among the 30 ischemic stroke patients 73% patient had carotid artery stenosis and most of the patient among them had smooth plaques 17 (57%) with 12(40%) calcified in nature and 20(67%) have centric in distribution. Conclusion: Carotid artery stenosis has a well-established association with ischemic stroke. Doppler studies are economic, safe, reproducible and less time consuming test to find out cerebrovascular insufficiency and recommended for primary and secondary prevention of ischemic stroke. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 06-09